Unveiling Interaction Dynamics: Exploring Novel Turn-Taking Strategies In The Ellen Degeneres Show - Dr. Naeem Fatima , Ayesha Waheed , Dr. Nailah Riaz (Migration Letters, 2024)
This study examines turn-taking methods in Hillary Clinton and Ellen DeGenere’s interactions on The Ellen Show. More specifically, the research examines how these strategies improve speech flow. These approaches are crucial to conversational coherence and order. Ellen DeGeneres and Hillary Clinton used different turn-taking strategies in their interactions, and this study identifies and analyzes them. Conversation analysis defines turn-taking as switching roles between speaker and listener after each turn (Sacks, Schegloff, & Jefferson 1984). This study used qualitative data from YouTube footage of Hillary Clinton’s guest appearances on The Ellen Show. These discussion transcripts were meticulously analyzed using Miles and Huberman (1994) and Saldana (2016) frameworks. The data show that these talks use three main turn-taking methods. These methods are "taking the floor," "holding the floor," and "yielding the floor," where a person [1]gives up their turn to let another speak. Notably, "yielding the floor" was the most common approach, accounting for 52% (66.6% of all instances). Due to its prevalence, efficient communication dynamics are advised, making it easy for Ellen DeGeneres to regulate the conversation and giving Hillary Clinton several chances to respond and interact authentically. In conclusion, this research illuminates the intricate mechanics of turn-taking in broadcast interviews. These data also show that these strategies help presenters and visitors interact coherently and engagingly.